Cloning of the xylanase gene from soil Streptomyces into Escherichia coli for the poultry industry application - BAHRAMINIA, M; MORADMAND, F; AMINI, K (Journal of the Hellenic Veterinary Medical Society, 2022)
Streptomyces are gram-positive aerobic strains that are isolated from soil, water, sediments, and various sources. The bacteria are capable of producing secondary metabolites, such as enzymes that sometimes play unique functional roles in industry, and are one of the important bio-control agents. This study aimed to isolate and clone thexylanase gene from soil Streptomyces. Soil samples were collected from Markazi Province, Iranafter specific biochemical examinations, isolation of bacteria, and DNA extraction. PCR was then performed to identify the strains containing the xylanase gene. The gene from the positive strains was cloned into an E.coli host-vector by TA cloning technique and finally, the expression of genes in E. coli origami was measured by Real-Time PCR technique. ClustalX and Mega5 software were used to draw the phylogenetic tree. A total of twelve Streptomyces isolates were identified from the soil samples. Among all the isolates, threeones had the xylanase gene. After cloning the xylanase genes, the cloned strains were isolated. To confirm the DNA cloning, Real-Time PCR was performed, and finally, the PCR product where sequenced. In this study, Streptomyces was identified as a native strain for the expression of xylanase after generating recombinant plasmid and TA cloning. It can be stated that cloning of the xylanase gene from soil Streptomyces in E. coli can be used in the poultry industry.